2001
DOI: 10.1074/jbc.m109551200
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Investigation of the Interaction of 1- and 2-Substituted 3-Hydroxypyridin-4-ones with 5-Lipoxygenase and Ribonucleotide Reductase

Abstract: The structural and physiochemical properties of 3-hydroxypyridin-4-one chelators (HPOs) which influence inhibition of the iron-containing metalloenzymes ribonucleotide reductase (RR) and 5-lipoxygenase (5-LO) have been investigated. HPOs with substituents at the 1-and 2-positions of the pyridinone ring have been synthesized, and their inhibitory properties compared with those of desferrioxamine (DFO). Varying the alkyl substituents does not affect the affinity constant of these ligands for iron(III), but permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…In this regard, cell lines selected for resistance to hydroxyurea have been shown to possess increased RRM2 protein levels and ribonucleotide reductase activity (16 -18). Other more recently characterized inhibitors also predominantly inhibit RRM2 (19,20). By contrast, previous studies with bacterial ribonucleotide reductase have shown that 2Ј-substituted diphosphate nucleosides may directly interfere with the RRM1 subunit.…”
Section: Introductionmentioning
confidence: 87%
“…In this regard, cell lines selected for resistance to hydroxyurea have been shown to possess increased RRM2 protein levels and ribonucleotide reductase activity (16 -18). Other more recently characterized inhibitors also predominantly inhibit RRM2 (19,20). By contrast, previous studies with bacterial ribonucleotide reductase have shown that 2Ј-substituted diphosphate nucleosides may directly interfere with the RRM1 subunit.…”
Section: Introductionmentioning
confidence: 87%
“…During the hypoxia phase, xanthine dehydrogenase is converted to xanthine oxidase and concentrations of xanthine oxidase substrates (that is, hypoxanthine) are increased [32,43]. Once reoxygenation occurs, activated xanthine oxidase uses available oxygen and hypoxanthine to produce superoxide [26].…”
Section: Discussionmentioning
confidence: 99%
“…Klein et al [36] demonstrated that an oral dose of 50 mg/kg/day adequately inhibits xanthine oxidase activity in a rat model. However, previous work indicates that hypoxia upregulates xanthine oxidase activity [31,32]; therefore, we used a higher dose (65 mg/kg/day) in order to inhibit the increased xanthine oxidase activity resulting from intermittent hypoxia. Rats receiving vehicle received equivalent daily oral gavage volumes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cell lines selected for resistance to hydroxyurea, increased RRM2 protein levels and ribonucleotide reductase activity were detected (29-31). Taken together, these findings suggest that alterations in RRM1 and RRM2 expression may confer resistance to chemotherapy and may be useful biomarkers for predicting and monitoring responses to various therapies including Triapine Âź (32, 33). Pooled analyses from 40 different tumor samples obtained at baseline in 3 studies evaluating Triapine Âź at our institution showed that RRM2 protein and gene expression varied by tumor type following treatment with Triapine Âź (data not shown) (18, 19).…”
Section: Discussionmentioning
confidence: 79%